Kajian Eksperimental Penggunaan Katalisator Broquet Terhadap Performansi Mesin Otto Berkapasitas 113 cc - Rio Andi Saputra; Mulfi Hazwi (Retii, 2016)
In this study we are conduting research on the effects of the use of a catalyst (Broquet) and also emission levels exhaust of motorcycle 113 cc fuel capacity which use Premium RON 88 and Pertamax RON 92 as fuel. This study also to do a comparison of engine performance (torque,power specific fuel consumption,thermal efficiency,air fuel ratio) The result obtained the engine performance was increased by using soaked fuel with broquet. By using premium the torque increase up to 5 % , The power increase up to 5.2 %  SFC decrease of 12 %while using pertamax the torque increase of 1 %, power increase of 1 % SFC decrease of 3 %. The emission of exhaust Reduce by using soaked fuel with broquet. While using premium the content of CO was decrease of 30%, HC decrease of  11 % and CO2 increase of 38 %. By using pertamax the content of  CO was decrease of 10 %, HC decrease of  19 % and CO2 increase of 9  % Keywords: engine performance, Broquet catalytic,catalyst.